Knowledge sharing practices in a local public training institute - Liaw, Annie (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study explores knowledge sharing practices in a public training institute in Sarawak, from the aspects of the importance of knowledge sharing, types of knowledge shared, problem faced in knowledge sharing, ways to promote knowledge sharing, and the personality traits of knowledge sharers in the institute. This study is conducted qualitatively. The sampling method used is purposive sampling based on informants’ demographic backgrounds and job descriptions. Eight informants were involved in providing data through open-ended survey and personality tests. This study has successfully met the research objectives. The importance of knowledge sharing, the types of knowledge shared, the problem faced in knowledge sharing, ways to promote knowledge sharing, and personality traits of knowledge sharers are identified and discussed extensively in the report. The findings of this research contribute to the knowledge, the practitioners, methodology and the policy related to knowledge sharing. It also comes out with recommendations for future researchers and the top management to enhance knowledge sharing in the organization.